Single cell RNA sequencing analysis of mouse cochlear supporting cell transcriptomes with activated ERBB2 receptor indicates a cell-specific response that promotes CD44 activation - Piekna-Przybylska, Dorota; Na, Daxiang; Zhang, Jingyuan; Baker, Cameron; Ashton, John M.; White, Patricia M. (Frontiers in Cellular Neuroscience, 2023)
Hearing loss caused by the death of cochlear hair cells might be restored through regeneration from supporting cells via dedifferentiation and proliferation, as observed in birds. In a previous report, ERBB2 activation in a subset of cochlear supporting cells promoted widespread down-regulation of SOX2 in neighboring cells, proliferation, and the differentiation of hair cell-like cells. Here we analyze single cell transcriptomes from neonatal mouse cochlear supporting cells with activated ERBB2, with the goal of identifying potential secreted effectors. ERBB2 induction in vivo generated a new population of cells with de novo expression of a gene network. Called small integrin-binding ligand n-linked glycoproteins (SIBLINGs), these ligands and their regulators can alter NOTCH signaling and promote cell survival, proliferation, and differentiation in other systems. We validated mRNA expression of network members, and then extended our analysis to older stages. ERBB2 signaling in young adult supporting cells also promoted protein expression of gene network members. Furthermore, we found proliferating cochlear cell aggregates in the organ of Corti. Our results suggest that ectopic activation of ERBB2 signaling in cochlear supporting cells can alter the microenvironment, promoting proliferation and cell rearrangements. Together these results suggest a novel mechanism for inducing stem cell-like activity in the adult mammalian cochlea.